활액성 육종의 증례 보고 - 이백수(Baek-Soo Lee); 최근락(Keun-Lak Choi); 오정환(Jung-Hwan Oh); 이상철(Sang-Chull Lee); 김여갑(Yeo-Gab Kim); 류동목(Dong-Mok Ryu); 권용대(Yong-Dae Kwon); 김시영(Si-Young Kim) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2004)
A malignant sarcoma of soft tissue that arises near but not in a joint, most often in an adolescent or young adult, is typically slow-growing, and may escapes notice until it causes pain. The diagnosis of this tumor can be suspected by X-ray or imaging, made by biopsy, and confirmed by chromosome studies. Cytogenic studies reveal a translocation between the X chromosome and chromosome 18 in the tumor cells. The most common treatment for the tumor is surgery to remove the entire tumor, nearby muscle, and lymph nodes. Synovial sarcoma tends to recur locally and to involve regional lymph nodes. Distant metastasis occurs in half cases. The well-documented and adequately followed cases are currently lacking and this report described an instance of Synovial sarcoma good result after treatment and review of literature. KCI Citation Count: 0